2021
DOI: 10.1111/1365-2656.13457
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and fur colouration: Testing the camouflage and thermoregulation hypotheses in an Arctic mammal

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Although the proximate factors driving these trends are likely complex and not well understood (e.g. camouflage, thermoregulation, immune response and genetic rescue effects) [19,37], our results suggest that brown-on white mismatch does not significantly penalize or outweigh the potential benefits of the blue morph phenotype [19,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the proximate factors driving these trends are likely complex and not well understood (e.g. camouflage, thermoregulation, immune response and genetic rescue effects) [19,37], our results suggest that brown-on white mismatch does not significantly penalize or outweigh the potential benefits of the blue morph phenotype [19,38].…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary mechanisms underlying Arctic fox fur coloration are not well studied and the main difference between the colour morphs is thought to be their camouflage value in different habitats [ 34 ]. Recently, Di Bernardi et al [ 69 ] also showed fitness advantages in Norwegian blue foxes. However, the performance of the two colour morphs was not differentially affected by the tested climatic variables (snow cover and winter temperature), except for a weak indication of thermal advantage of blue juveniles, with a tendency of higher survival in colder winter temperatures compared to white juveniles [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Di Bernardi et al [ 69 ] also showed fitness advantages in Norwegian blue foxes. However, the performance of the two colour morphs was not differentially affected by the tested climatic variables (snow cover and winter temperature), except for a weak indication of thermal advantage of blue juveniles, with a tendency of higher survival in colder winter temperatures compared to white juveniles [ 69 ]. Overall, they did not find consistent evidence that these advantages are owing to differences in camouflage or thermoregulation [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, camera traps might be used to study the presence of predators and prey of the leucistic carnivores, making it possible to infer how hunting success and survival might differ in populations with leucistic individuals compared to populations without. Lastly, camera traps can be used to monitor badger sets to study the number of offspring and offspring survival of sets with or without leucistic badgers, to derive estimates of fitness consequences of fur coloration (Bernardi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%